Digital Health Literacy and Cognitive Learning Outcomes Among Pre-Service Primary School Teachers in Indonesia - Elinda Rizkasari; Prima Trisna Aji; Arief Shofyan Baidhowy (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
Objectives: This study aims to examine the relationship between digital health literacy and cognitive learning outcomes among pre-service primary school teachers in Indonesia. Methods: A quantitative approach with a correlational design was employed. The population consisted of all students enrolled in the Primary School Teacher Education (PGSD) Program at Universitas Slamet Riyadi, Surakarta. A proportionate stratified random sampling technique was used, and a total of 30 students participated as respondents and completed the research instruments. Digital health literacy was measured using the Digital Health Literacy Instrument (DHLI), while cognitive learning outcomes were obtained from official academic records of core courses. Findings: Descriptive analysis showed that the mean score of students’ digital health literacy was 95.27 (SD = 3.41) with a score range of 90-100. The mean score of cognitive learning outcomes was 94.83 (SD = 3.42) with a score range of 90-99. The results of the Pearson correlation test indicated that there was no significant relationship between digital health literacy and cognitive learning outcomes (r = -0.03; p = 0.893). Similarly, the Spearman rho test confirmed the absence of a significant association (ρ = -0.08; p = 0.686). These findings suggest that, statistically, there is insufficient evidence to conclude a relationship between the two variables within the context of this study. Conclusion: Although the statistical tests did not show a significant relationship between digital health literacy and cognitive learning outcomes, the high mean scores on both variables indicate that the students demonstrated good levels of digital health literacy as well as strong cognitive learning outcomes. Future studies involving larger samples and additional relevant variables are recommended to obtain a more comprehensive understanding of the factors influencing cognitive learning outcomes among pre-service primary school teachers.